Penerapan Model Pembelajaran Latihan Penelitian untuk Meningkatkan Penguasaan Konsep IPA Di SD 1 Gondoharum Kudus - Yuni Ratnasari (Universitas Sebelas Maret, 2017)
This research aims to 1) determine the effects of the implementation of learning models of research exercises to increase mastery of Science concepts in Elementary School 1 Gondoharum Kudus. 2) knowing the effectiveness of research exercise models to enhance the mastery of Science concepts. The Research Exercise Model has five steps namely facing problems, finding and studying data, studying data and experimentation, formulating problems and stage analyzing. Mastery of Science concepts is the teacher's ability to overcome basic concepts of Science in the cognitive, affective and psychomotor areas. This study used a quasiexperiment one group pretest posttest research design completed with descriptive analysis. The subjects of this research are students of IVA and IVB SDN 1 Gondoharum Jekulo Kudus. Data collection techniques used test, observation, worksheet, and documentation data. Conceptmastery is obtained from pretest and posttest results. Pretest and posttest scores are analized with descriptive statistics including mean, median, standard of devisation, sknewness andpercentiles. Then, normality and homogeneity tests are performed as a requirement for the t-test using the paired sample t-test. The Success of this research is seen from the effect of application of Research Exercise Learning toward Mastery of Science Concept which is indicated by T-test results sig. (2-tailed) value of 0.35 <0.05. From the result, it can be concluded that there is a significant difference on post student test data between experiment and control classes. The difference showed that mastery of the concept of experimental class is better than the control class. The effectiveness of implementing Research Exercises Learning to Improve the mastery of the Science concept increased by 13.7 average score of pre test to post test.